Comparison of Plasma Free Fatty Acids Between Hyperemesis Gravidarum and Normal Pregnancy [318]. (May 2015) - Ozturk, Mustafa; Ulubay, Mustafa; Ozturk, Ozlem; Aydin, Hakan; Keskin, Ugur; Yenen, Mufit C.
Abstract : OBJECTIVE: We aimed to compare the levels of plasma free fatty acids between healthy pregnant patients and those with hyperemesis gravidarum. METHODS: The study enrolled 52 patients. Of these, 26 patients known to have hyperemesis gravidarum between 7 and 12 weeks of gestation constituted the study group and 26 patients, who were healthy pregnant women in the same weeks of gestation, were recruited as the control group. Saturated fatty acids, C14, C15, C16, C18, C20, C22, C24, monounsaturated fatty acids, C18:1n9 (oleic acid), C22:1n9 (erucic acid), C24:1n9 (nervonic acid), omega 3 free acids, C22:5n3 (eicosapentaenoic acid), C22:6n3 (docosahexaenoic acid), omega 6 free acids, C18:2n6 (linoleic acid), C20:4n6 (arachidonic acid), and C20:3n6 (homogamma-linolenic acid) were evaluated by gas chromatography–flame ionization detector. RESULTS: There was no statistical significant difference between the groups on the basis of age, gestational week, or plasma level of eicosapentaenoic acid, docosahexaenoic acid, or archidonic acid. There was a statistically significant difference between the groups on the basis of plasma level of C20 (arachidic acid) and C22 (behenic acid). C20 reduced, but the level of C22 behenic acid increased in the hyperemesis gravidarum group. CONCLUSION: Hyperemesis gravidarum did not affect the plasma levels of eicosapentaenoic acid, docosahexaenoic acid, or archidonic acid, which contribute to placental and fetal neurologic development. We detected that hyperemesis gravidarum affects the plasma levels of C20 (arachidic acid) and C22 (behenic acid). To supply energy needs, plasma levels of C20 may be decreased. C22 behenic acid is a cholesterol-raising saturated fatty acid in humans. The reason for the increase of C22 in the hyperemesis group should be investigated.